Hydrophobic Actuation of a DNA Origami Bilayer Structure1. Issue 16 (11th March 2014) - List, Jonathan; Weber, Michael; Simmel, Friedrich C.
Abstract Amphiphilic compounds have a strong tendency to form aggregates in aqueous solutions. It is shown that such aggregation can be utilized to fold cholesterol‐modified, single‐layered DNA origami structures into sandwich‐like bilayer structures, which hide the cholesterol modifications in their interior. The DNA bilayer structures unfold after addition of the surfactant Tween 80, and also in the presence of lipid bilayer membranes, with opening kinetics well described by stretched exponentials. It is also demonstrated that by combination with an appropriate lock and key mechanism, hydrophobic actuation of DNA sandwiches can be made conditional on the presence of an additional molecular input such as a specific DNA sequence.